Low levels of Plasmodium falciparum parasitaemia among patients receiving antiretroviral therapy at the treatment centre of the Regional Hospital Bamenda, Northwest Cameroon. - Calvin Bisong Ebai; Cedric Yamssi; Flore Nguemaïm Ngoufo; Nicaise Ngouemeta Tchoffo; Omarine Nfor Nlinwe; Helen Kuokuo Kimbi (PLoS ONE)
Background Malaria and HIV are leading causes of death in Africa, including Cameroon. Antiretroviral therapy (ART) is expected to boost immunity and reduce vulnerability to opportunistic infections. Reports on comorbidities including malaria are common in Cameroon. Objectives To determine the prevalence of malaria parasitaemia, clinical manifestations, treatment related factors and prevention methods associated with malaria parasitaemia as well as parasite density among HIV patients on ART. Methods It was a cross-sectional study among HIV patients on ART at the Regional Hospital Bamenda. A pre-tested questionnaire was used to collect data on participants' socio-demographic characteristics, clinical manifestations, history of HIV treatment and malaria prevention methods. Microscopy was used for malaria parasite diagnosis and to determine white blood cell (WBC) count. Data was analysed using SPSS version 20. Results The study included 181 participants. The overall prevalence of malaria parasitaemia was 9.4%. Although there were no significant statistical differences, the following trends were observed in the results: 55-71 year old age group (14%) was most infected with malaria parasite with the highest prevalence among those on the 8A first-line ART (10.3%, 14/122); (χ2=1.03, p=0.96), only participants in the 8A and 12A ART protocols were infected; parasite prevalence was higher in patients with detectable viral load (14.3%, 3/21), (OR=.0.57 (CI: 0.15-2.2), p=0.41), while GMPD varied from 45.7-53.3-±23.1/μl of blood. Conclusion Low malaria parasite prevalence and density were detected amongst HIV patients receiving ART. A systematic malaria test could be helpful to avert morbidity and improve the general health of patients on ART.